Translation and validation of Chinese version of sense of competence in dementia care staff scale in healthcare providers: a cross-sectional study - Yayi Zhao; Li Liu; Yaping Ding; Ye Shan; Helen Y. L. Chan (BMC Nursing, 2022)
Abstract Background Healthcare providers’ dementia-care competence is crucial for quality dementia care. A reliable and valid instrument is needed to assess the gaps in their dementia-care competence, and thereby identifying their educational needs. Therefore, this study aims to translate the 17-item Sense of Competence in Dementia Care Staff (SCIDS) scale into Chinese (SCIDS-C) and to validate the SCIDS-C among Chinese healthcare providers. Methods The translation procedure followed the modified Brislin’s translation model. A cross-sectional survey was conducted using the translated version. The validity, including content validity, confirmatory factor analysis, concurrent validity and known-groups validity, was tested. Reliability in terms of internal consistency and test-retest reliability with a 2-week interval was evaluated. Results A total of 290 healthcare providers in 12 nursing homes and a hospital completed the survey. The scale-level content validity index was .99. The confirmatory factor analysis model marginally supported the original 4-factor structure. Positive but weak correlations were noted between the total score of the SCIDS-C and that of the Dementia Knowledge Assessment Scale (r = .17, p = .005) and Approaches to Dementia Questionnaire (r = .22, p < .001), suggesting acceptable concurrent validity. Differences between health professionals and care assistants were significant in two subscales scores. The internal consistency of the scale was high, with Cronbach’s α of .87. Test-retest reliability was demonstrated with intra-class correlation coefficient of 0.88. Conclusions The SCIDS-C demonstrated acceptable reliability and validity although the known-groups validity between health professionals and care assistants was not fully established. It can be used to measure the level of sense of competence and as an outcome measure in educational intervention aiming at improving dementia care among Chinese healthcare providers.